Preparation method of ultra-dispersed nano titanium carbide particle reinforced titanium-based composite material
By using uniform mixing of sub-ten nanoscale graphene suspension and titanium matrix powder in titanium-based composite materials and subsequent sintering and thermal deformation treatment, the in-situ self-generating and uniform distribution of nano-titanium carbide particles is achieved, solving the problem of insufficient strength and plasticity of traditional titanium-based composite materials under room temperature conditions, and significantly improving the overall performance of the material.
Patent Information
- Application Number
- CN202510090896.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
AI Technical Summary
The titanium-based composite materials prepared by traditional smelting technology have abnormal coarsing of the reinforcement body during high-temperature cooling, and the tendency of self-aggregation of ceramic particles has not been effectively solved, resulting in poor strength and plasticity of the material under room temperature conditions.
The sub-ten nanoscale graphene suspension is uniformly mixed with the titanium matrix powder, and after molding, vacuum microwave sintering and extrusion hot deformation treatment, the uniform distribution of in-situ self-generated nanotitanium carbide particles in the titanium-based composite material is achieved.
The complete coherence relationship between the in-situ self-generating nano-titanium carbide particles and the titanium matrix is achieved, the strength and plasticity of the material are improved, and the interface bonding force and uniform deformation ability are enhanced.
Smart Images

Figure CN119899954A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of titanium-based composite materials, in particular to a method for preparing a super-dispersed nano titanium carbide particle reinforced titanium-based composite material. Background Art
[0002] Titanium alloys have the characteristics of low density, high specific strength, and good heat resistance. They are widely used in key components such as aircraft engine turbine blades and high-pressure compressor disks, and have gradually become one of the irreplaceable key strategic materials in major national equipment fields such as aerospace. Using discontinuous high-strength ceramics to compositely strengthen titanium alloys and designing and developing discontinuously reinforced titanium-based composites (TMCs) is an important means to improve the performance of titanium alloys. However, TMCs prepared by traditional smelting technology usually lead to abnormal coarsening of the reinforcements due to the need for a slow cooling process at high temperatures, making the reinforcements appear to be micron-sized, and as their volume fraction increases, the tendency of ceramic particles to self-agglomerate in the melt has never been effectively solved. Generally, the strengthening effect of micron-sized reinforcements mainly comes from the load transfer from the matrix to the reinforcement phase during loading. However, under the influence of stress concentration and weak interface bonding between the reinforcement phase and the matrix, the stress transfer and transfer effects are not ideal. In addition, micron-sized reinforcements that tend to be distributed at grain boundaries will induce stress concentration in the matrix, forming defects and cracks and leading to intergranular fracture, resulting in poor strength and plasticity of the material at room temperature, limiting the further development and application of TMCs.
[0003] In order to solve the weak interface bonding between the reinforcement phase and the matrix and the strengthening limitations of micron-scale reinforcements, researchers have induced the reinforcement behavior of the reinforcement phase to evolve from load transfer to dislocation strengthening (Orowan) mechanism by reducing the size of the reinforcement phase, thereby effectively improving the mechanical properties of the composite material. However, direct external reinforcements usually introduce interfacial impurities such as oxygen or other contaminants, resulting in poor interface bonding of the composite material, and problems such as agglomeration defects in nanoscale reinforcements, making it impossible to achieve effective comprehensive performance improvement. Compared with the external addition method, in-situ synthesized ceramic reinforcements have become the preferred method for preparing high-performance TMCs due to the advantages of clean interface between the reinforcement and the matrix, good interface bonding, and uniform dispersion of the reinforcement phase. Therefore, it is of great significance to study and develop in-situ self-generated nanoscale reinforcements to strengthen TMCs so that they have both excellent strength and plasticity. Summary of the invention
[0004] Based on this, it is necessary to provide a method for preparing ultra-dispersed nano-titanium carbide particle-reinforced titanium-based composite materials, which can achieve uniform distribution of in-situ self-generated nano-titanium carbide in the matrix crystal, and the prepared titanium-based composite materials have excellent strength and plasticity, and the process flow is simple. The following is a specific technical solution.
[0005] A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material comprises the following steps:
[0006] Providing sub-10 nanometer flake graphene suspension;
[0007] The titanium matrix powder and the sub-10 nanometer flake graphene suspension are uniformly mixed, and then dried to obtain a mixed powder of sub-10 nanometer flake graphene and titanium matrix;
[0008] The mixed powder is molded and then vacuum microwave sintered to obtain a sintered blank;
[0009] The sintered blank is subjected to extrusion heat deformation treatment to obtain an ultra-dispersed nano titanium carbide particle reinforced titanium-based composite material.
[0010] In one embodiment, the titanium matrix powder is pure titanium powder, Ti-50Nb alloy powder, Ti-6Ni-4Zr-2Mo alloy powder or Ti-6Al-4V powder.
[0011] In one of the embodiments, the method for achieving uniform mixing of the titanium matrix powder and the sub-ten nanometer flake graphene suspension is specifically: adding the titanium matrix powder to the sub-ten nanometer flake graphene suspension, and mixing evenly using electromagnetic stirring; the rate of the electromagnetic stirring is 300r / min~900r / min, and the time is 10~60 minutes.
[0012] In one of the embodiments, the compression molding steps are specifically as follows: setting the pre-pressure to 20MPa-40MPa, gradually pressurizing to 100MPa-300MPa at a pressurization rate of 50MPa / min-200MPa / min, maintaining the pressure for 30-90 minutes, and gradually reducing the pressure.
[0013] In one embodiment, the vacuum microwave sintering steps are specifically as follows: preset microwave power of 0.5kw~4.0kw, initial vacuum degree ≤5Pa, heating to 800℃~1200℃ at a heating rate of 100℃ / min~200℃ / min, keeping warm for 30~90 minutes, and cooling with the furnace.
[0014] In one embodiment, the extrusion thermal deformation treatment step is specifically as follows: preheating the sintered blank to 800°C to 1200°C, keeping the extrusion barrel at a temperature of 600°C to 800°C, an extrusion ratio of 33 to 16:1, and an extrusion rate of 5 mm / s to 15 mm / s.
[0015] In one embodiment, the sub-ten nanometer flake graphene suspension is prepared by the following method:
[0016] Providing sub-10 nanometer flake graphene particles;
[0017] The sub-10-nanometer flaky graphene particles are uniformly dispersed in an alcohol solvent to obtain a sub-10-nanometer flaky graphene suspension.
[0018] In one embodiment, the sub-ten nanometer flake graphene particles are prepared by the following method:
[0019] Provide micron-scale flake graphite;
[0020] The micron-sized flake graphite and an alcohol solvent are mixed and subjected to ultrasonic treatment for 10 to 60 minutes to obtain a mixed solution;
[0021] The mixed solution is mechanically ball-milled, filtered, and dried to obtain the sub-ten-nanometer flaky graphene particles.
[0022] In one embodiment, the mechanical ball milling step is specifically as follows: using anhydrous ethanol as a mixing medium, ball-to-material ratio of 5 to 20:1 at a rotation speed of 200 rpm to 400 rpm for 6 to 24 hours, and then continuing to ball mill at a rotation speed of 400 rpm to 600 rpm for 6 to 48 hours.
[0023] Beneficial effects:
[0024] (1) The above method uses sub-ten-nanometer flake graphene as a carbon source, which can in situ self-generate nanoscale titanium carbide (TiC) with a titanium matrix. The TiC inherits the extremely fine nanometer size of the original carbon source, and can realize the preparation of sub-ten-nanometer TiC particles.
[0025] (2) The above method can realize the in-situ self-generation of sub-ten-nanometer TiC particles within the crystal, and form a completely coherent relationship with the titanium matrix, giving TiC a strong interface bonding force, which can give full play to the strengthening advantages of nano-reinforcements and improve the uniform deformation capacity of the composite material.
[0026] (3) The ultra-dispersed nano-TiC reinforced titanium-based composite material prepared by the above method can fully utilize the Orowan strengthening effect of TiC distributed in the crystal, effectively improve the storage capacity of matrix dislocations, and greatly promote the simultaneous improvement of the strength and toughness of the composite material.
[0027] (4) The above method is simple to operate, highly practical and universal. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a TEM (transmission electron microscope) image of the sub-ten-nanometer flake graphene particles prepared in step (1) of Example 1.
[0029] Figure 2 This is a SEM (scanning electron microscope) image of the mixed powder prepared in step (2) of Example 1.
[0030] Figure 3This is a TEM image of the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material prepared in step (4) of Example 2.
[0031] Figure 4 This is a comparison chart of tensile properties tests of the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite materials prepared in Examples 1 to 4 and pure titanium. DETAILED DESCRIPTION
[0032] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively below, and preferred embodiments of the present invention are provided. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0033] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0034] A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material according to one embodiment includes the following steps S110 to S140:
[0035] S110, providing a sub-ten nanometer flake graphene suspension.
[0036] In this embodiment, the sub-ten nanometer scale graphene suspension is prepared by the following steps (S1101-S1102):
[0037] S1101. Provide sub-ten-nanometer flake graphene particles.
[0038] In this embodiment, sub-10 nanometer scale graphene particles are prepared by the following steps (1) to (3):
[0039] (1) Providing micron-sized flake graphite;
[0040] (2) mixing the micron-sized flake graphite and an alcohol solvent (such as ethanol, butanol, propylene glycol, etc.), and ultrasonically treating for 10 to 60 minutes to obtain a mixed solution;
[0041] (3) After mechanical ball milling, the mixed solution is filtered and dried to obtain sub-ten-nanometer flaky graphene particles.
[0042] The mechanical ball milling step in step (3) is specifically as follows: using anhydrous ethanol as a mixed medium, ball milling at a ball-to-material ratio of 5 to 20:1 at a rotation speed of 200 rpm to 400 rpm for 6 to 24 hours, and then continuing to ball mill at a rotation speed of 400 rpm to 600 rpm for 6 to 48 hours.
[0043] The drying method in step (3) is specifically: drying by evaporation using a rotary evaporator.
[0044] By adopting the above steps (1) to (3), sub-ten-nanometer flaky graphene particles with uniform particle size and excellent self-dispersibility can be prepared.
[0045] It should be noted that the sub-ten-nanometer flaky graphene particles are not limited to being prepared by the above steps, but can also be obtained by other existing methods, as long as sub-ten-nanometer flaky graphene particles with uniform particle size and excellent self-dispersibility can be obtained.
[0046] S1102, uniformly dispersing the above-mentioned sub-10 nanometer flaky graphene particles in an alcohol solvent to obtain a sub-10 nanometer flaky graphene suspension.
[0047] In this embodiment, the sub-10 nanometer flake graphene particles are uniformly dispersed by ultrasonic dispersion in an alcohol solvent (such as ethanol, butanol, propylene glycol, etc.) to obtain a sub-10 nanometer flake graphene suspension.
[0048] It can be understood that, in addition to ultrasonic dispersion, other methods that can achieve uniform dispersion of sub-ten-nanometer flaky graphene particles in alcohol solvents are all acceptable.
[0049] S120, uniformly mixing the titanium matrix powder and the above-mentioned sub-ten nanometer flake graphene suspension, and drying to obtain a mixed powder of sub-ten nanometer flake graphene and titanium matrix.
[0050] In this embodiment, the titanium matrix powder is pure titanium powder, Ti-50Nb alloy powder, Ti-6Ni-4Zr-2Mo alloy powder or Ti-6Al-4V alloy powder.
[0051] It is understood that there is no particular limitation on the shape of the titanium matrix powder, and it may be in the form of flakes, spheres or any irregular shapes, depending on the titanium matrix powder available on the market.
[0052] Specifically, the method for achieving uniform mixing of the titanium matrix powder and the sub-ten-nanometer flake graphene suspension in step S120 is: adding the titanium matrix powder to the sub-ten-nanometer flake graphene suspension, and mixing evenly using electromagnetic stirring; the rate of the electromagnetic stirring is 300r / min to 900r / min, and the time is 10 to 60 minutes.
[0053] Furthermore, the drying method in step S120 is: rotary evaporation drying. Specifically, the uniformly mixed titanium matrix and sub-10 nanometer scale graphene suspension are placed in a rotary evaporation bottle and rotated at a speed of 20r / min to 200r / min in a constant temperature water bath at 30°C to 80°C for 1 to 6 hours.
[0054] It can be understood that the drying in step S120 is mainly used to remove the solvent, and is therefore not limited to the drying method described above, and other methods that can remove the solvent without affecting the powder state are also acceptable.
[0055] S130, molding the mixed powder and then sintering it by vacuum microwave to obtain a sintered blank.
[0056] In this embodiment, the steps of compression molding are specifically as follows: setting the pre-pressing pressure to 20MPa~40MPa, gradually pressurizing to 100MPa~300MPa at a pressurizing rate of 50MPa / min~200MPa / min, maintaining the pressure for 30~90 minutes, and gradually reducing the pressure.
[0057] In this embodiment, the vacuum microwave sintering steps are specifically as follows: preset microwave power is 0.5kw~4.0kw, initial vacuum degree ≤5Pa, heating to 800℃~1200℃ at a heating rate of 100℃ / min~200℃ / min, keeping warm for 30~90 minutes, and cooling with the furnace.
[0058] Through vacuum microwave sintering, sub-ten-nanometer flake graphene as a carbon source can in situ self-generate nanoscale titanium carbide on a titanium matrix. The titanium carbide inherits the extremely fine nanometer size of the original carbon source and can effectively realize the preparation of sub-ten-nanometer titanium carbide particles.
[0059] S140, subjecting the sintered blank to an extrusion heat deformation treatment to obtain an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material.
[0060] In this embodiment, the extrusion thermal deformation treatment step in step S140 is specifically as follows: preheating the sintered blank to 800°C to 1200°C, keeping the extrusion barrel at 600°C to 800°C, the extrusion ratio at 33 to 16:1, and the extrusion rate at 5 mm / s to 15 mm / s.
[0061] The sintered blank is subjected to extrusion heat deformation treatment, so that the in-situ self-generated nano-scale titanium carbide can be evenly distributed in the matrix crystal during large extrusion deformation.
[0062] By adopting the above steps S110 to S140, the in-situ self-generation of sub-ten-nanometer titanium carbide particles within the crystal can be achieved. The in-situ self-generated sub-ten-meter titanium carbide particles can form a completely coherent relationship with the titanium matrix, have a strong interface bonding force, can give full play to the strengthening advantages of the nano-reinforcement body, and improve the uniform deformation ability of the composite material.
[0063] At the same time, the ultra-dispersed titanium carbide particle reinforced titanium-based composite material prepared by the above steps S110 to S140 can fully utilize the Orowan strengthening effect of the titanium carbide distributed in the crystal, effectively improve the storage capacity of matrix dislocations, and greatly promote the simultaneous improvement of the strength and toughness of the composite material.
[0064] The following are specific embodiments.
[0065] Example 1
[0066] A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material, the specific steps are as follows:
[0067] (1) Preparation of sub-10 nanometer flake graphene: Micron-sized flake graphite and ethanol were mixed and ultrasonically treated for 10 minutes to obtain a mixed solution; the mixed solution was mechanically ball-milled (using anhydrous ethanol as the mixing medium, with a ball-to-material ratio of 5:1 at a speed of 200 rpm for 6 hours, and then continued to ball-mill at a speed of 400 rpm for 6 hours), filtered, and dried to obtain sub-10 nanometer flake graphene particles.
[0068] (2) Preparation of mixed powder: Add 0.5 g of the above-mentioned sub-10 nanometer flaky graphene particles into 2000 mL of ethanol solution, and ultrasonically disperse them at 1000 W of ultrasonic power for 30 min to obtain a sub-10 nanometer flaky graphene suspension; add 100 g of spherical pure Ti powder to the above suspension, mix them evenly using electromagnetic stirring (the electromagnetic stirring rate is 300 r / min, and the time is 60 min), and dry them to obtain a mixed powder of sub-10 nanometer flaky graphene and titanium.
[0069] (3) Vacuum microwave sintering: 100 g of the mixed powder was molded (pre-pressure was set at 20 MPa, and the pressure was gradually increased to 100 MPa at a pressure rate of 50 MPa / min, and the pressure was maintained for 30 min; then the pressure was gradually reduced to complete the pressing of the powder mixture) and then vacuum microwave sintered (the preset microwave power was 0.5 kW, the initial vacuum degree was ≤5 Pa, the temperature was increased to 800 °C at a heating rate of 100 °C / min, and the temperature was maintained for 30 min, and then cooled in the furnace) to obtain a sintered blank.
[0070] (4) Extrusion thermal deformation: The sintered blank was preheated to 800°C, and the temperature of the extrusion barrel was maintained at 600°C. Hot extrusion was performed at an extrusion ratio of 33:1 and an extrusion rate of 5 mm / s to obtain an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material.
[0071] Depend on Figure 1 and Figure 2It can be seen that the synthesized sub-10 nanometer scale graphene has an extremely fine nanoparticle size (average particle size is about 4.5nm) and exhibits good self-dispersion in aqueous solution. When used as a reinforcing material in a composite material, the unique nanoparticle size can regulate the size of the in-situ self-generated TiC particles.
[0072] from Figure 2 It can be seen that after stirring and mixing, the pure titanium powder and the sub-ten nanometer flake graphene are evenly mixed, and the sub-ten nanometer flake graphene is evenly dispersed on the surface of the titanium powder without obvious agglomeration.
[0073] It should be noted that Figure 1 NFG stands for sub-ten nanometer flake graphene; Figure 2 NFG / Ti powders refers to a mixed powder of sub-ten-nanometer flake graphene and titanium matrix.
[0074] Example 2
[0075] A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material, the specific steps are as follows:
[0076] (1) Preparation of sub-10 nanometer flake graphene: Micron-sized flake graphite and ethanol were mixed and ultrasonically treated for 20 minutes to obtain a mixed solution; the mixed solution was mechanically ball-milled (with anhydrous ethanol as the mixing medium, at a ball-to-material ratio of 10:1 at a rotation speed of 250 rpm for 12 hours, and then continued to ball-mill at a rotation speed of 450 rpm for 8 hours), filtered, and dried to obtain sub-10 nanometer flake graphene particles.
[0077] (2) Preparation of mixed powder: 0.5 g of the above-mentioned sub-10 nanometer flake graphene particles were added to 2000 mL of ethanol solution, and ultrasonically dispersed at 1000 W ultrasonic power for 30 min to obtain a sub-10 nanometer flake graphene suspension; 100 g of flaky Ti-50Nb alloy powder was added to the above suspension, mixed evenly by electromagnetic stirring (the electromagnetic stirring rate was 400 r / min, and the time was 30 min), and dried to obtain a mixed powder of sub-10 nanometer flake graphene and Ti-50Nb alloy;
[0078] (3) Vacuum microwave sintering: 80 g of the mixed powder was molded (pre-pressure was set at 30 MPa, and the pressure was gradually increased to 150 MPa at a pressure rate of 70 MPa / min, and the pressure was maintained for 45 min; then the pressure was gradually reduced to complete the pressing of the powder mixture) and then vacuum microwave sintered (pre-set microwave power was 1.0 kW, initial vacuum degree ≤ 5 Pa, and the temperature was increased to 880°C at a heating rate of 120°C / min, and the temperature was maintained for 45 min, and then cooled with the furnace) to obtain a sintered blank;
[0079] (4) Extrusion thermal deformation: The sintered blank is preheated to 900°C, and the temperature of the extrusion barrel is maintained at 700°C. Hot extrusion is performed at an extrusion ratio of 24:1 and an extrusion speed of 7 mm / s to obtain an ultra-dispersed titanium carbide reinforced titanium-based composite material.
[0080] from Figure 3 It can be seen that after thermal deformation, the uniform distribution of nano-TiC within the crystal can be effectively achieved. During the thermal deformation process, the nano-scale in-situ self-generated TiC reinforcement particles migrate along the grain boundaries and separate from the grain boundaries in the grains, and are often concentrated in the crystal. This unique reinforcement distribution form can simultaneously exert the advantages of grain boundary strengthening effect and intracrystalline strengthening effect, which is beneficial to simultaneously improve the strength and plasticity of titanium-based composites.
[0081] It should be noted that Figure 3 NFG / Ti composite refers to ultra-dispersed nano-titanium carbide particle reinforced titanium matrix composite material.
[0082] Example 3
[0083] A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material, the specific steps are as follows:
[0084] (1) Preparation of sub-10 nanometer flake graphene: Micron-sized flake graphite and ethanol were mixed and ultrasonically treated for 30 minutes to obtain a mixed solution; the mixed solution was mechanically ball-milled (with anhydrous ethanol as the mixing medium, at a ball-to-material ratio of 10:1 at a rotation speed of 350 rpm for 12 hours, and then continued to ball-mill at a rotation speed of 500 rpm for 24 hours), filtered, and dried to obtain sub-10 nanometer flake graphene particles.
[0085] (2) Preparation of mixed powder: 0.5 g of the above-mentioned sub-10 nanometer scale graphene particles were added to 2000 mL of ethanol solution, and ultrasonically dispersed at 1000 W ultrasonic power for 30 min to obtain a sub-10 nanometer scale graphene suspension; 100 g of spherical pure Ti powder was added to the above suspension, and mixed evenly by electromagnetic stirring (the electromagnetic stirring rate was 600 r / min, and the time was 20 min), and dried to obtain a mixed powder of sub-10 nanometer scale graphene and titanium;
[0086] (3) Vacuum microwave sintering: 100 g of the mixed powder was molded (pre-pressure was set at 30 MPa, and the pressure was gradually increased to 200 MPa at a pressure rate of 100 MPa / min, and the pressure was maintained for 60 min; then the pressure was gradually reduced to complete the pressing of the powder mixture) and then vacuum microwave sintered (pre-set microwave power was 2.0 kW, initial vacuum degree ≤ 5 Pa, and the temperature was increased to 1000 °C at a heating rate of 150 °C / min, and the temperature was maintained for 60 min, and then cooled in the furnace to obtain a sintered blank;
[0087] (4) Extrusion thermal deformation: The sintered blank was preheated to 800°C, and the temperature of the extrusion barrel was maintained at 700°C. Hot extrusion was performed at an extrusion ratio of 20:1 and an extrusion rate of 9 mm / s to obtain an ultra-dispersed nano-TiC reinforced titanium-based composite material.
[0088] Example 4
[0089] A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material, the specific steps are as follows:
[0090] (1) Preparation of sub-10 nanometer flake graphene: Micron-sized flake graphite and ethanol were mixed and ultrasonically treated for 60 minutes to obtain a mixed solution; the mixed solution was mechanically ball-milled (using anhydrous ethanol as the mixing medium, with a ball-to-material ratio of 20:1 at a speed of 400 rpm for 24 hours, and then continued to ball-mill at a speed of 600 rpm for 48 hours), filtered, and dried to obtain sub-10 nanometer flake graphene particles.
[0091] (2) Preparation of mixed powder: Add 0.5 g of the above-mentioned sub-10 nanometer flaky graphene particles into 2000 mL of ethanol solution, and ultrasonically disperse them at an ultrasonic power of 1000 W for 30 min to obtain a sub-10 nanometer flaky graphene suspension; add 100 g of spherical pure Ti powder to the above suspension, mix them evenly using electromagnetic stirring (the electromagnetic stirring rate is 900 r / min, and the time is 10 min), and dry them to obtain a mixed powder of sub-10 nanometer flaky graphene and titanium.
[0092] (3) Vacuum microwave sintering: 100 g of the mixed powder was molded (pre-pressure was set at 40 MPa, and the pressure was gradually increased to 300 MPa at a pressure rate of 200 MPa / min, and the pressure was maintained for 90 min; then the pressure was gradually reduced to complete the pressing of the powder mixture) and then vacuum microwave sintered (the preset microwave power was 4.0 kW, the initial vacuum degree was ≤5 Pa, the temperature was increased to 1200°C at a heating rate of 200°C / min, and the temperature was maintained for 90 min, and then cooled in the furnace) to obtain a sintered blank.
[0093] (4) Extrusion thermal deformation: The sintered blank was preheated to 1200°C, and the temperature of the extrusion barrel was maintained at 800°C. Hot extrusion was performed at an extrusion ratio of 16:1 and an extrusion speed of 15 mm / s to obtain an ultra-dispersed nano-titanium carbide reinforced titanium-based composite material.
[0094] The mechanical properties of the ultra-dispersed titanium carbide reinforced titanium-based composite materials prepared in Examples 1-4 were tested respectively, and the results are shown in Table 1.
[0095] Table 1
[0096] sample Room temperature yield strength Room temperature elongation Room temperature elongation Example 1 1000MPa 1063MPa 17.4% Example 2 980MPa 1050MPa 16.1% Example 3 960MPa 1030MPa 12.6% Example 4 1030MPa 1150MPa 16.8% Pure Titanium 680MPa 710MPa 9.8%
[0097] As can be seen from Table 1, the titanium-based composite material reinforced by in-situ self-generated ultra-dispersed nano-TiC can obtain excellent strength-shaping matching at room temperature, greatly improving the comprehensive performance of the composite material. The in-situ self-generated TiC reinforcement is evenly distributed in the crystal, which can serve as a site for dislocation proliferation and accumulation, improve the dislocation storage capacity of the composite material and alleviate the stress concentration during deformation to obtain a good elongation at break. At the same time, TiC forms a completely coherent relationship with the titanium matrix, giving TiC a strong interface bonding force, giving full play to the strengthening advantages of the nano-reinforcement, and improving the uniform deformation ability of the composite material.
[0098] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing an ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material, characterized in that: The following steps are involved: Providing sub-10 nanometer flake graphene suspension; The titanium matrix powder and the sub-10 nanometer flake graphene suspension are uniformly mixed, and then dried to obtain a mixed powder of sub-10 nanometer flake graphene and titanium matrix; The mixed powder is molded and then vacuum microwave sintered to obtain a sintered blank; The sintered blank is subjected to extrusion heat deformation treatment to obtain an ultra-dispersed nano titanium carbide particle reinforced titanium-based composite material.
2. The method for preparing the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material according to claim 1, characterized in that: The titanium matrix powder is pure titanium powder, Ti-50Nb alloy powder, Ti-6Ni-4Zr-2Mo alloy powder or Ti-6Al-4V alloy powder.
3. The method for preparing the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material according to claim 1, characterized in that: The method for achieving uniform mixing of the titanium matrix powder and the sub-ten-nanometer flake graphene suspension is specifically as follows: adding the titanium matrix powder to the sub-ten-nanometer flake graphene suspension and mixing uniformly using electromagnetic stirring; the electromagnetic stirring rate is 300r / min to 900r / min, and the time is 10 to 60 minutes.
4. The method for preparing the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material according to claim 1, characterized in that: The compression molding steps are specifically as follows: setting the pre-pressure to 20MPa-40MPa, gradually increasing the pressure to 100MPa-300MPa at a pressure rate of 50MPa / min-200MPa / min, maintaining the pressure for 30-90 minutes, and gradually reducing the pressure.
5. The method for preparing the ultra-dispersed titanium carbide particle reinforced titanium-based composite material according to claim 1, characterized in that: The vacuum microwave sintering steps are as follows: preset microwave power to 0.5 kW to 4.0 kW, initial vacuum degree ≤ 5 Pa, heating to 800°C to 1200°C at a heating rate of 100°C / min to 200°C / min, keeping the temperature for 30 to 90 minutes, and cooling with the furnace.
6. The method for preparing the ultra-dispersed titanium carbide particle reinforced titanium-based composite material according to claim 1, characterized in that: The steps of the extrusion thermal deformation treatment are specifically as follows: preheating the sintered blank to 800°C to 1200°C, keeping the extrusion barrel at a temperature of 600°C to 800°C, an extrusion ratio of 33 to 16:1, and an extrusion rate of 5 mm / s to 15 mm / s.
7. The method for preparing the ultra-dispersed titanium carbide particle reinforced titanium-based composite material according to any one of claims 1 to 6, characterized in that: The sub-10 nanometer scale graphene suspension is prepared by the following method: Providing sub-10 nanometer flake graphene particles; The sub-10-nanometer flaky graphene particles are uniformly dispersed in an alcohol solvent to obtain a sub-10-nanometer flaky graphene suspension.
8. The method for preparing the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material according to claim 7, characterized in that: The sub-10 nanometer scale graphene particles are prepared by the following method: Provide micron-scale flake graphite; The micron-sized flake graphite and an alcohol solvent are mixed and subjected to ultrasonic treatment for 10 to 60 minutes to obtain a mixed solution; The mixed solution is mechanically ball-milled, filtered and dried to obtain the sub-ten-nanometer flaky graphene particles.
9. The method for preparing the ultra-dispersed nano-titanium carbide particle reinforced titanium-based composite material according to claim 8, characterized in that: The mechanical ball milling step is specifically as follows: using anhydrous ethanol as a mixed medium, ball milling at a ball-to-material ratio of 5 to 20:1 at a rotation speed of 200 rpm to 400 rpm for 6 to 24 hours, and then continuing to ball mill at a rotation speed of 400 rpm to 600 rpm for 6 to 48 hours.
Citation Information
Cited By
Preparation method of particle reinforced Ti-based composite material laminated plate
CN120756181A